Electromagnetic-thermal multi-physics coupling simulation of cable joints: considering contact resistance and typical defects - Wu, Lifang; Jin, Qingren; Yu, Xiaoyong; Zhang, Biyun (Frontiers in Energy Research, 2024)
As the "artery" of the urban power grid, high-voltage cables and their operating status are directly related to grid safety. Cable joint is a weak part of cable line prone to defects, leading to cable failure and jeopardizing the power supply reliability. This study constructs a three-dimensional electromagnetic-thermal multi-physics coupling model of cable joint for the analysis of contact resistance and typical insulation defects. Using an equivalent conductivity model, the thermal loss and temperature distribution of the joint were investigated under different contact coefficients. Subsequently, models for air-gap defect and water tree defect in cable joints were established to simulate the temperature and electric field distribution under these conditions. The simulation results indicate that, at an ambient temperature of 25℃, the contact resistance of a 110 kV high-voltage AC cable joint significantly increases the loss density, raising the joint temperature much higher than cable body, while not altering the temperature gradient distribution. Small air-gap has minimal impact on the temperature distribution of joint insulation but causes significant electric field distortion up to 8 kV/mm. Water tree defect considerably affects both temperature and electric field, causing a 20℃ temperature rise and a 30 kV/mm electric field distortion. This research reveals the strong influence of contact resistance and water tree defect on cable joints, quantifying the resulting hazards like loss increase, temperature rise and electric field distortion.